Gabon : Second and Third Reviews Under the Stand-By Arrangement and Requests for Waiver of Nonobservance of Performance Criteria and Modification of Performance Criterion; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Gabon. (IMF Staff Country Reports; Country Report ;, 2009)
This paper presents key findings of the Second and Third Reviews for Gabon under the Stand-By Arrangement. Performance under the program has been mixed. Non-oil economic growth was robust prior to the onset of the international financial crisis, spurred by high oil and commodity prices. However, little progress has been made to bring the non-oil fiscal deficit to a sustainable position. IMF staff supports the authorities' request for waivers for nonobservance of the performance criteria and recommends completion of the second and third reviews.